What Does Tirpitz’s Naval Programme Reveal About the Political Culture of the Kaiserreich? - Coppola, Salvatore (InterSedes, 2013)
Admiral Alfred von Tirpitz’s naval programme reveals a number of underlying features which are unique aspects of the political culture of the Kaisereich; both in the domestic and international contexts. The naval arms-race against Great Britain was an event that resulted from the interaction of a number of goals that Tirpitz had initially envisaged for Germany and Kaiser William II. Yet, the pursuit of an ever-greater navy fleet was by no means a monopoly of the Germans but, on the contrary, it was a common trait of every major European Power of the time, from Britain to Austria, to Russia. Nevertheless, the scale to which Tirpitz went deserves a particular emphasis in that it was not only a military programme, but rather, its aims were directed towards the achievement of objectives in a number of fields: economic growth, domestic socio-political stability, and German Imperialism through Weltpolitik, which reflected the contemporary political issues present within the Kaiserreich. These three aspects will be explored with further emphasis on the structural aspects of the Wilhelmine system of government together with the individuals that were involved in German policymaking at the time. It will therefore be possible to observe how these various features were crucial in determining Germany’s political system. This, in turn, allowed Tirpitz’s radical and militaristic plan to take place. The Tirpitz Plan reveals its objectives as being not solely restricted to the military-naval domain. Furthermore, one will see how the Tirpitz plan could have taken place only in Germany during the Kaiserreich thanks to the uniquely ambiguous administrative structures Germany possessed.